2010
DOI: 10.1089/jwh.2009.1733
|View full text |Cite
|
Sign up to set email alerts
|

Educating Hispanic Women About Breast Cancer Prevention: Evaluation of a Home-Based Promotora-Led Intervention

Abstract: Participation in home-based group educational interventions delivered by promotoras may be associated with improved breast cancer screening practices among Hispanic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…De Alba et al 30 and Garbers et al 31 reported that lower participation rates are primarily associated with low socio-economic levels and health care barriers. Women believe that child-care issues influence the lack of follow-up mammograms 32,33,34,35 . Our results of asset index and having children, as factors influencing mammography participation are consistent with previous studies 6,28,29,30,32,33,34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Alba et al 30 and Garbers et al 31 reported that lower participation rates are primarily associated with low socio-economic levels and health care barriers. Women believe that child-care issues influence the lack of follow-up mammograms 32,33,34,35 . Our results of asset index and having children, as factors influencing mammography participation are consistent with previous studies 6,28,29,30,32,33,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Women believe that child-care issues influence the lack of follow-up mammograms 32,33,34,35 . Our results of asset index and having children, as factors influencing mammography participation are consistent with previous studies 6,28,29,30,32,33,34,35 . As Brouwers et al 36 reported, there is no evidence that group education has an effect on mammography adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of key breast cancer prevention messages and subsequent SBE in community-based breast cancer prevention interventions among low-income women greatly depend on the extent to which community leaders are involved in participant recruitment, organization, and conduction of these interventions [4,12,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Key components of the program include educational workshops, mammogram referrals, and a multimedia campaign. Further, delivering the care in their community, especially culturally friendly locations such as individual's homes and familiar community-based organizations, works to ensure a positive reception and improved breast cancer screening practices among Hispanic women [18].…”
Section: The Yo Me Cuido ® Programmentioning
confidence: 99%